Simple power analysis attack against cryptosystems based on Montgomery algorithm - Gang GAN; Min WANG; Zhi-bo DU; Zhen WU (Tongxin xuebao)
The Montgomery algorithm is widely used to reduce the computational complexity of large integer modular exponentiation. The SPA (simple power analysis) attacks against public-key cryptosystems based on Montgomery algo-rithm implementation were presented by exploitation of the inherent security vulnerability which that sensitive informa-tion leakage could be used by side-channel attack. The chosen-message SPA attacks were focused on, which enhance the differences of operating wave-forms between multiplication and squaring correlated to the secret key by using the input of particular messages. In particular, a SPA attack against RSA cryptosystem was showed based on large integer modular exponentiation. The results show that the attack algorithm is correct and effective.